The preparation of a composite stabilate for immunisation against East Coast fever - Morzaria, S.P.; Spooner, P.R.; Bishop, Richard P.; Mwaura, S. (International Livestock Research Institute, 1999)
The preparation of Theileria parva stabilates has been described by Cunningham et al (1973). The method is detailed in the FAO report (1978) and the FAO tick and tick-borne Disease Manual (1984). Theileria parva stabilates are a source of viable sporozoites that can be used to immunise cattle by infection and treatment After the development of the infection and treatment method of immunisation in the mid-1970s, an immunising stabilate referred to as the 'Mugugu cocktail', comprising three stocks of T. parva-Mugugu, Kiambu S and Serengeti-transformed was prepared. ILRI was requested by FAO to prepare a batch of the 'Mugugu cocktail'. This paper describes the detailed protocol for the preparation and the in vitro and in vivo characterisations of the composite stabilate, designated FAO 1.